PENENTUAN JUMLAH TENAGA KERJA OPTIMAL BAGIAN PEMANENAN BERDASARKAN ANALISIS BEBAN KERJA DI PT. EQUALINDO MAKMUR ALAM SEJAHTERA - Elisa Herawati; Fathiah; M. Taury Rafly (JURNAL AGRIMENT, 2020)
Each division in the company has a different workload size so that a different workload calculation is needed in determining the effective and efficient time for workers in their field of work with predetermined targets. Workload analysis can provide information on the completion time of work that can be achieved by each workforce so that it can be seen how much optimal workforce is needed by the company to achieve the predetermined target. Equalindo Makmur Alam Sejahtera is engaged in the oil palm plantation industry with the main activity of the company is to develop, plant, care for and harvest oil palm fresh fruit bunches (FFB). In oil palm plantation companies, harvesting activities are one of the determinants of company productivity, therefore researchers try to identify the workload and calculate the optimal number of harvesting workers at PT. equalindo Makmur Alam Sejahtera division 1 part of harvesting. This study aims to determine the time for completing the work of the main tasks assigned, perform workload analysis to determine optimal labor requirements, and determine policies that need to be done to improve the performance of labor in harvesting so that moreeffective and efficient. The method used in this study was the observation of the work activities of 16 harvesting workers with the following research procedures; Calculating Effective Working Days per month, Calculating productive Working Time, Calculating Work Completion Time (WPK) and Calculating Labor Needs Optimal. The conclusion of this research is the number of WPK harvesting part is 108,772 minutes/year or 227 days/year and the optimal number of labor as a result of the calculation is 13 people.